Association of α-SMA and EpCAM Expressions with Recurrence Risk Based on Histopathological Subtypes of Basal Cell Carcinoma - Yona, Fajriza; Hilbertina, Noza; Mulyani, Henny; Bachtiar, Hafni (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2024)
Background Basal cell carcinoma (BCC) is the most common skin malignancy in the world with a proportion 70%. Recurrent and aggressive variants are still challenging in diagnosis and treatment. Histopathologically, there are two group of BCC risk of recurrence, i.e low risk and high risk. Assessment the expression of alpha-smooth muscle actin (α-SMA) as a biomarker of cancer associated fibroblast cell in stroma and the expression of epithelial cell adhesion molecule (EpCAM) in tumor cells probably have role in the pathomechanism of BCC progression, suggest its can distinguish the risk of BCC recurrence. This research aims to determine the assosiation between the expression of α-SMA and EpCAM with the recurrence risk group of BCC histopathological subtypes. Methods This was a cross sectional study using 48 samples, with 24 low and high risk groups each. Histopathological subtypes were determined from Hematoxylin and eosin slide. The expression of α-SMA and EpCAM was examined by the immunohistochemical method which was assessed semiquantitatively. Statistical analysis was performed using the Chi-square test with p<0.05 was considered significant. Results Expression of α-SMA with the score 3 was found more in high risk BCC (85.7%), while a score of 1 was more in low risk BCC (100%). Loss of EpCAM expression was mainly found in high risk BCC (82.8%). Statistical analysis showed that there was a significant assosiation between the expression of α-SMA and EpCAM and the recurrence risk group of BCC histopathological subtypes with p value =0.000 for each. Conclusions This study concluded that increased of α-SMA expression and loss of EpCAM expression were associated with a high recurrence risk group of BCC histopathological subtypes.